Application of Ethanol Extracts From Alnus sibirica Fisch. ex Turcz in Hair Growth Promotion - Ha, Eun Ju; Yun, Jang-Hyuk; Si, Chuanling; Bae, Young Soo; Jeong, Young-Hwan; Park, Kwang-Hyun; Choi, Sun-Eun (Frontiers in Bioengineering and Biotechnology, 2021)
Alnus sibirica Fisch. ex Turcz (ASFT), belonging to the family of Betulaceae, grows naturally in Asia, Europe, and America. The aims of this study are determining the efficacy of various biomarkers related to hair loss, evaluated by extracting the branch with 60% alcohol, and purely separating diarylheptanoid oregonin, an indicator and active substance, from 60% alcohol extract of the tree. To determine the preventive effects on hair loss, we investigated the anti-oxidative and anti-apoptotic effects on hydrogen peroxide-induced cytotoxicity on human hair dermal papilla cells using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay and Western blotting analysis for proving of apoptosis-related marker alteration, respectively. Moreover, we examined the ameliorative effects of 60% alcohol extract of the tree and oregonin against changes of oxidative stress-induced cytokine and testosterone-induced dihydrotestosterone production as crucial pathways of the hair loss mechanism. These results suggest that 60% alcohol extract of the tree and oregonin were available as novel natural materials for maintaining hair health in mammals.